Living Experience of Tobanese Etnict with Post- Coronary Artery Bypass Graft in Medan, Indonesia - Amnita Anda Yanti Ginting; Nurmaini Nurmaini; Nur Asnah Sitohang (International Journal of Nursing and Health Services (IJNHS), 2020)
Coronary heart disease (CHD) is the leading cause of death and disability worldwide. The study aimed to explore patients experience postoperative coronary artery bypass graft among the Toba tribe. A qualitative study design with a descriptive phenomenology approach was applied in this study. Fifteen participants were selected by purposive sampling based on the criteria inclusion people. Two central themes were obtained from the analysis, including 1) lifestyle changed and 2) Cultural Traditions Batak Toba. Participants felt better after undergoing CABG surgery. They change a better lifestyle by eating healthy, reducing cholesterol-containing foods such as Toba Batak ethnic foods, and not consuming alcoholic beverages (wine). Also, they exercise regularly, stop smoking and prevent stress. Toba Batak cultural traditions after CABG surgery get mangupa-upa tradition by giving the whole diarsik goldfish, giving Ulos sampetua, Boras warden nitondi aimed to nourish the spirits and souls of participants who are recovering from illness. The results of this study can be input to the nurse in the care of patients post-CABG Batak Toba.